Perspectives of the influence of social determinants on health empowerment: a qualitative study of tribal women in Udaipur, north India - Thakur, Ravinder (Social Determinants of Health, 2021)
Background: Improvement in the women’s health promotes the sustainable development goal of good health and well-being. Providing equal opportunities and access to the resources would not empower women unless they are given more autonomy and power to take decisions. The current study explored the viewpoints of women about the influence of structural, socio-cultural determinants on health understanding and decision making. Methods: An exploratory qualitative study design and interpretive epistemological approach were used to conduct the study among purposively selected16 adult women in Udaipur sub division located in the Trans Himalayan region of north India. Data was analyzed using the thematic content analysis and constant comparative approach. Results: Based on the similarities and commonalities of the responses of the participants four broader themes and ten subthemes were identified. The study found that determinants like socioeconomic conditions, poor health literacy, less autonomy, housing conditions, harsh winters and distance negatively affect women’s health. Women identified health illiteracy, time, and lack of basic health facilities as the barriers to access the healthcare system. Conclusion: The study results recommended the need for early inclusion of women as one of the stakeholders of health system. Participatory approach by health professionals can build the trust between the health care system and women. On policy level the government needs to improve the education for girls, employment and health infrastructure. More studies on women’s perspectives towards underlying social determinants would be required for better health policies.